Home Groceries Management System Using IOT - T. , Manikandan; D. , Tamil Selvan; R. , Vaidhyanathan; B. , Vigneshvaran; V. , Nandalal (International Journal of Psychosocial Rehabilitation, 2020)
In this fast world, remembering the groceries in the the kitchen is really a tough job for the people who are involved in jobs away from home. To get rid of these things, a smart kitchen shelf system will keep track of the availability of the grocery items in the kitchens at home. This work is aimed at detecting the groceries that are to be refilled and intimates the user with an alert through a webpage. In this work we used a load cell to collect the information about the weight of the grocery items/products, with the help of an analog-to-digital converter and NodeMCU modules. The designed system is connected with the internet via WiFi, which will intimate the family head/user whenever the weight of the products goes below the threshold level.